A comprehensive study on bid-ask spread and its determinants in India - Aritra Pan; Arun Kumar Misra (Cogent Economics & Finance, 2021)
Determinants of bid-ask spread have been explored significantly for low-frequency datasets in many developed markets. Researchers have identified share price, traded volume, market-capitalization, return volatility, and number of trades as the prime spread drivers. However, the validity of these determinants has not been explored in high-frequency trading. The present study attempts to articulate the validity of low-frequency determinants of the bid-ask spread in high-frequency trading. It used "bigglm" concept to estimate various determinants of spread, one of the study's major contributions. The study found a positive relation between market-capitalization and spread, supporting the theory that a higher trading volume cannot decrease the bid-ask spread. Explanatory variables are all significant and show different impacts in different market conditions and sectors. For pooled data, share price, traded volume, quote return, trading frequency, and return volatility are in inverse relation with the spread. The study investigates sectoral determinants of the bid-ask spread to understand sector-specific influences. It also explores the influence of up and down market, settlement cycles, opening and closing intervals, and price and market-cap on determinants. The findings have significance regarding influence on the market microstructure for trading, designing of trading liquidity, and reduction of transaction cost.
Keywords: 330; bid-ask spread; bigglm; High-Frequency trading; market determinants; market microstructure